KAJIAN KUAT LENTUR BALOK BETON BERTULANGAN BAMBU PETUNG TAKIKAN TIPE V DENGAN JARAK 2 CM DAN 3 CM - Fitra Ameldi; Agus Setiya Budi; Supardi Supardi (Matriks Teknik Sipil, 2014)
In the construction industry, concrete reinforced steel is a construction material that is commonly used in building structures, where the compressivestrength of concrete and the tensile strength of steel is a combination that complement each other. However, using steel as reinforcement still get someconstraints amongst the price more higher and that is a product of the mining which unrenewable and someday will runs out. To resolve theseconstraint, as an alternative solution to replace steel reinforcement, then utilized bamboo, where bamboo is a natural product which renewable,easily to get, inexpensive, and have a high tensile strength. from that idea, This research was conducted to determine the yield strength of bamboopetung used for analysis and the flexural capacity of the beam Reinforced bamboo petung, by making beam specimen a total of 12 pieces withdimention of 11 cm x 15 cm x 170 cm. Three of the first beam specimen planted reinforcement bamboo petung notches type V with distance 2 cmand 3 cm for the next beam specimen, The next three beam specimens planted reinforcement steel ø 8 mm and three beam specimen unreinforcedfor comparison. Testing was conducted in Structures laboratory, FT UNS, at the age of concrete 28 days with giving two concentrated loads pointsat a distance of 1/3 span beam from toehold. Based on the analysis and test results can be concluded, yield strength of bamboo petung obtained at223.893 N/mm2 or a tensile strength on nodia, because the tensile strength on nodia at least half of the tensile strength in internodia. For theflexural capacity of test results, flexural capacity of beam reinforced bamboo petung notches with distance 2 cm greater 4,04% than beam reinforcedsteel ø 8 mm, while for beam reinforced bamboo petung notches 3 cm obtained 2.424% larger than the beam reinforced steel ø 8 mm. From the12 pieces specimen beams, average collapse occurs in the area 1/3 middle span beams and can said to be as the collapse of flexible. With thisexperimental test results of the beams reinforcement bamboo petung notches type V with distance 2 cm and 3 cm sufficient potential as areplacement for steel reinforcement on a simple building.